UPAYA PEMBERDAYAAN MASYARAKAT MELALUI PENGHIMPUNAN DANA KOINISASI DI DESA NGRONGGOT KECAMATAN NGRONGGOT KABUPATEN NGANJUK - Moh. Hasyim Afandi; Zainal Arifin; Tri Wahyudi Ramdhan (As-Sidanah, 2020)
Nahdlatul Ulama, the majority of whose members are mostly from the lower class, initiated to collect coins from members. All members are asked to participate. Therefore Board of Management of Nahdlatul Ulama Nganjuk regency launched the NU Caring Coin Movement program. It is the movement of NU members to collect coins from the homes of residents of Nahdliyin whose benefits are to solve various problems in aspects of life and realize the independence of jam'iyyah. The results of the mentoring activities obtained were first, the condition of Ngronggot village society before the mentoring although the spirit of diversity and social solidarity was very high but still individual. Second, The form of the assistance activities carried out included awareness of their potential so that they always think positively, and vocational training the following applications so that new interpreneurs emerge. Third, after the mentoring program is complete, community trust in self potential, both economic and religious, emerges together to support each other both in religious and social activities.